To solve the problem, we need to understand what it means for ray AC to bisect angle A.
Given:
- Ray AC bisects ∠A
- m∠BAD = 46 degrees
Since ray AC bisects ∠A, this means that it divides ∠A into two equal parts:
\[ m∠BAC = m∠DAC \]
Now, let's denote the measures of the angles:
\[ m∠BAC = x \]
Since ray AC bisects ∠A, then:
\[ m∠DAC = x \]
The total measure of angle A is the sum of these two angles:
\[ m∠A = m∠BAC + m∠DAC = x + x = 2x \]
We know that the measure of one part, m∠BAD, is 46 degrees. In this scenario, it's not given that m∠BAD is equal to m∠BAC, but rather that angle B refers to angle A's composition. We can set up an equation to relate what we know about angles A and B.
Since m∠BAD + m∠DAC = m∠A:
\[ m∠BAD + m∠BAC = 2x \]
Given that m∠BAD = 46 degrees, we can state:
\[ 46 + x = 2x \]
Rearranging gives us:
\[ 46 = 2x - x \] \[ x = 46 \]
This means:
\[ m∠BAC = 46 \text{ degrees} \]
Thus, the correct answer is:
The m∠BAC is 46 degrees.